Draft Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Volume-XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1985)
This region being comparatively backward in the field science and Technology as compared to the rest of the Country, the State Department of Science, Technology and Environment is committed to promote science and Technology Programme in the Hill Areas to ameliorate the quality of life of those who have not been able to enjoy the fruits of such development.
Office of the Development Commissioner for the Hill Areas of Assam